ANALYSIS OF CORRECTIVE MAINTENANCE MONITOR CCA TOOL DVOR SELEX TYPE-1150A - Abrar, Raihan; Fatonah, Feti; Dayanthi, Adenia Kusuma; Syahputra, M. Efaldes (Journal of Airport Engineering Technology (JAET), 2024)
In the aviation industry, navigation has a crucial role in supporting the smooth running of flight routes to maintain the safety and security of air transportation. Perum LPPNPI Pekanbaru branch provides communication, Navigation, Surveillance, and Data Processing facilities to ensure flight safety, regularity, and comfort. One of the navigation facilities available at Perum LPPNPI Pekanbaru branch is the Doppler VHF-Omnidirectional Range (DVOR), an air navigation system control tool that can guide aircraft to land precisely at the destination airport by providing information in the form of azimuth or artificial bearing. This research aimed to analyze the care and maintenance system for DVOR equipment, and identify several potential problems that have arisen during the operation of DVOR equipment at Perum LPPNPI Pekanbaru branch. In this research, evaluations and observations were carried out to assess the level of DVOR maintenance in accordance with Advisory Circular CASR Part 171-12. This research focused on evaluating Corrective Maintenance Monitor (CMM) analysis on DVOR Selex Type-1150A equipment at Perum LPPNPI Pekanbaru Branch. DVOR is a critical air navigation system that requires effective corrective maintenance. The method used in the research is procedural analysis of equipment maintenance as in research conducted by Widasari Mutiara, this research also focused on CMM evaluation, identification of potential problems, and performance analysis to improve maintenance efficiency. Research adopted a qualitative research method with a descriptive approach, because the data collected is textual in nature. This research method involved CMM system inspection, equipment maintenance analysis, and interviews with engineering personnel. The research results provide insights for improving corrective maintenance procedures, and increasing the availability and reliability of the DVOR system. The implications of these findings support safe and reliable flight operations at Perum LPPNPI Pekanbaru Branch.